Kepemimpinan Kewirausahaan Kepala Sekolah Di SMKS Putra Nusantara 4 Kabupaten Bengkulu Tengah - Suprapto (UNIVERSITAS BENGKULU, 2023)
The research design used in this study was descriptive-qualitative. The problem to be studied is what is the innovation, creativity and responsibility of entrepreneurial leadership towards the policies implemented? The purpose of the research is the application of Entrepreneurial Leadership Innovation, creativity created and applied and the responsibilities of Entrepreneurial Leadership. The results of the observations show that the Principal has kept up with the times by participating in reporting programs and work programs using internetization, has implemented Entrepreneurial Leadership by creating various innovations that are useful for school development, the Principal has also innovated creatively and has good responsibilities in carrying out his main duties and functions as Principal